2018
DOI: 10.5811/westjem.2018.9.38865
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Patient Satisfaction with Treatment of Low-risk Pulmonary Embolism

Abstract: IntroductionMany emergency department (ED) patients with acute pulmonary embolism (PE) who meet low-risk criteria may be eligible for a short length of stay (LOS) (<24 hours), with expedited discharge home either directly from the ED or after a brief observation or hospitalization. We describe the association between expedited discharge and site of discharge on care satisfaction and quality of life (QOL) among patients with low-risk PE (PE Severity Index [PESI] Classes I–III).MethodsThis phone survey was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Second, we disseminated quarterly research reports to the ED physicians with updates of our ongoing PE studies (Figure 1). Continued research from our own practice setting on the safety and effectiveness of outpatient management for patients with acute PE may have helped communicate that this was becoming a systemwide standard of care …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we disseminated quarterly research reports to the ED physicians with updates of our ongoing PE studies (Figure 1). Continued research from our own practice setting on the safety and effectiveness of outpatient management for patients with acute PE may have helped communicate that this was becoming a systemwide standard of care …”
Section: Methodsmentioning
confidence: 99%
“…There is no prompt or best-practice alert. RISTRA-PE includes an autopopulating version of the validated PE Severity Index (eTable 1 in the Supplement) 8,31,32,55 with risk-based recommendations to inform site-of-care decision-making (Table 1) and outpatient exclusion criteria modeled after the Canadian criteria and Hestia clinical decision rule (eFigure in the Supplement). 34,35 Our site-of-care recommendations were designed to be assistive, not directive (eAppendix 3 in the Supplement).…”
Section: Activation Of Ristra-pe After Diagnostic Confirmation Of Pe ...mentioning
confidence: 99%
See 1 more Smart Citation
“…One survey of emergency physicians found that lack of clear follow-up was the single biggest barrier to outpatient PE treatment, 23 and successful outpatient PE treatment programs described in the literature ensured follow-up with an appropriate clinician after ED discharge. 19,26,92 A patient who is unlikely to follow up after a PE or DVT is not a good candidate for ED discharge.…”
Section: 53mentioning
confidence: 99%
“…Prompt diagnosis, risk assessment and adequate treatment can improve the outcome (7). A reliable risk stratification of PE severity based on the 2019 ESC Guidelines, pulmonary embolism severity index (PESI) or simplified PESI (sPESI) indicates risk of early (inhospital or 30-day) death (8)(9)(10)(11). Adding biomarkers data may help in improving prognosis and categorization of patients with acute PE into risk classes (11)(12).…”
Section: Introductionmentioning
confidence: 99%